Immunomodulation of J774A.1 Murine Macrophages by Lactiplantibacillus plantarum Strains Isolated From the Human Gastrointestinal Tract and Fermented Foods - Garcia-Gonzalez, Natalia; Nuñez-Sanchez, María A.; Villoria Recio, Miguel; Battista, Natalia; Gahan, Cormac G. M.; Corsetti, Aldo (Frontiers in Microbiology, 2021)
Lactobacillus plantarum species (recently re-named Lactiplantibacillus (Lpb.) plantarum subsp. plantarum) can be isolated from both either the mammalian gut or specific fermented foods where they may be present at high concentrations. Whilst Lpb. plantarum strains have been proposed as potential probiotic candidates, the ability of resident strains consumed in fermented foods to interact with the host is unclear. The main objective of this study was to investigate the cellular location and ability of three different food-borne Lpb. plantarum strains isolated from different sources (table olives and cheese) to modulate the immune response of a murine macrophage-like cell line (J744A.1). For that purpose, macrophages were exposed to the three different Lpb. plantarum strains for 24 hours and the expression of a panel of genes involved in the immune response, including genes encoding pattern-recognition receptors (TLRs and NLRs) and cytokines was evaluated by qRT-PCR. We also utilised chemical inhibitors of intracellular pathways to gain some insight into potential signalling mechanisms. Results showed that the native food strains of Lpb. plantarum were able to modulate the response of J774A.1 murine macrophages through a predominately NOD signalling pathway that reflects the transient intracellular location of these strains within the macrophage. The data indicate the capacity of food-dwelling Lpb. plantarum strains to influence macrophage-mediated host responses if consumed in sufficient quantities.